Requiem for the College Women's Gymnasium: Disciplining the Female Body in Educational and Architectural Space. Issue 14 (22nd September 2017) - Vertinsky, Patricia
Abstract: The women's college gymnasium's geographical, architectural and spatializing arrangements have historically been important ingredients in the social constitution of the gendered body. It has provided a critical stage on which struggles within the profession of physical education and its relation to competitive sport have been enacted both within its own boundaries and at the level of the broader campus and its shifting priorities. This paper explores the rise and demise of women's gymnasia on North American college campuses from the late nineteenth to the latter decades of the twentieth century to illuminate how the shifting academic landscape has reflected changing attitudes towards the perceived needs of female students and the nature of their training in physical education and movement sciences. The analysis focuses upon two women's colleges in the United States remarkable for their architectural splendour and programme integrity: the University of California at Berkeley's Phoebe Apperson Hearst Memorial Gymnasium for Women and the Anna Hiss Gymnasium at the University of Texas, Austin. It laments their gradual demise as academic institutions have increasingly shifted their priorities and the world of the female gymnasium has retracted to be reinserted into college campuses' twenty-first century vision for student recreation and competitive sport.